1988
DOI: 10.1016/0006-2952(88)90139-6
|View full text |Cite
|
Sign up to set email alerts
|

Non-xanthine heterocycles: Activity as antagonists of A1 and A2-adenosine receptors

Abstract: A variety of non-xanthine heterocycles were found to be antagonists of binding of [ 3 H]phenylisopropyladenosine to rat brain A 1 -adenosine receptors and of activation of adenylate cyclase via interaction of N-ethylcarboxarnidoadenosine with A 2 -adenosine receptors in human platelet and rat pheochromocytoma cell membranes. The pyrazolopyridines tracazolate, cartazolate and etazolate were several fold more potent than theophylline at both A 1 -and A 2 -adenosine receptors. The pyrazolopyridines, however, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 42 publications
2
44
0
Order By: Relevance
“…1). Second, tracazolate levels at its AD 50 value are associated with 270% enhancement of ␣ 1 ␤ 1 ␥ 2 GABA A Rs, which may result from its opposing action mediated by adenosine A 1 and A 2 receptors (Daly et al, 1988). Tracazolate is an antagonist of adenosine A 1 and A 2 receptors, with micromolar potency where it is predicted to promote arousal and wakefulness (Van Dort et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…1). Second, tracazolate levels at its AD 50 value are associated with 270% enhancement of ␣ 1 ␤ 1 ␥ 2 GABA A Rs, which may result from its opposing action mediated by adenosine A 1 and A 2 receptors (Daly et al, 1988). Tracazolate is an antagonist of adenosine A 1 and A 2 receptors, with micromolar potency where it is predicted to promote arousal and wakefulness (Van Dort et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, it would be desirable to develop a selective, potent, and bioavailable non-xanthine adenosine antagonist. A number of classes of non-xanthine adenosine antagonists have been discovered [32]. Of these, CGS 15943A, 14 ( Fig.…”
Section: Adenosine Antagonistsmentioning
confidence: 99%
“…8 We have found that the presence of chained alkyl groups (e.g. isopropyl) at the 6-and 7-positions enhance the potency of binding to A 1 receptors in this series.…”
Section: Resultsmentioning
confidence: 73%
“…1). Although xanthines are the classical adenosine antagonists, numerous classes of nonxanthine antagonists, 1,8 mainly fused nitrogen-containing heterocyclic structures, have been reported. Xanthines have, however, proven to be either inactive at cloned rat A 3 receptors, or relatively inactive at the sheep and human cloned A 3 receptors.…”
Section: Introductionmentioning
confidence: 99%